2020
DOI: 10.1101/2020.05.22.20109900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating Under Reporting of Leprosy in Brazil using a Bayesian Approach

Abstract: Leprosy remains an important health problem in Brazil - the country register the second largest number of new leprosy cases each year, accounting for 14% of the world's new cases in 2019. Although there was increasing advances in leprosy surveillance worldwide, the true number of leprosy cases is expected to be much larger than the reported. Leprosy underreporting impair planning effective interventions and thoughful decisions about the distribution of financial and health resources. In this study, we estimate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Raw data are shown in this figure and available at https://github.com/cidacslab/Estimating-under-reporting-of-leprosy-in-Brazil.git [ 31 ]. We produced the maps using R software, geobr package [ 31 , 32 ], (MIT license https://ipeagit.github.io/geobr/ ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raw data are shown in this figure and available at https://github.com/cidacslab/Estimating-under-reporting-of-leprosy-in-Brazil.git [ 31 ]. We produced the maps using R software, geobr package [ 31 , 32 ], (MIT license https://ipeagit.github.io/geobr/ ).…”
Section: Resultsmentioning
confidence: 99%
“…We used R software, geobr package, (MIT license https://ipeagit.github.io/geobr/ ) to create the maps produced in this work to visualise the spatial analysis, see [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…4 8 Failure to detect leprosy cases and the subsequent under-reporting of the disease can occur for a variety of reasons, including the low capacity of healthcare services or health professionals to diagnose and register new cases of the disease, lack of specific leprosy programmes and policies, absent or inadequate national disease registries and deficiencies in national or local leprosy programmes. 9 Models predicting the incidence or prevalence of cases of leprosy can facilitate the identification of new or undetected cases and inform health decision-making in respect of the target population for treatment and disease control and prevention actions. 7 Various prognostic modelling studies of leprosy cases have been reported in the literature, but they have been undertaken in a diverse range of settings using distinct approaches to predict cases.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, some countries are still facing some challenges in developing a mathematical model that provides an estimate of undetected incident cases that can approximate the reality of cases (4,8). Undetected cases or underreporting cases of leprosy can occur for many reasons, including the low capacity of health care services or health professionals to diagnose and register new cases of the disease, lack of speci c leprosy programs and policies, absence or poor national disease registries, or de ciencies of national or local leprosy programs (9). Models predicting the incidence or prevalence of cases of leprosy can facilitate the identi cation of new or undetected cases and inform health decision-making regarding the target population for treatment and disease control, and prevention actions (7).…”
Section: Introductionmentioning
confidence: 99%
“…Models predicting the incidence or prevalence of cases of leprosy can facilitate the identi cation of new or undetected cases and inform health decision-making regarding the target population for treatment and disease control, and prevention actions (7). Several forecasting modeling studies of leprosy cases have been reported in the literature, however, there are distinct approaches and settings for predicting the cases (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%